2019
DOI: 10.1186/s12936-019-3017-2
|View full text |Cite
|
Sign up to set email alerts
|

Protection induced by malaria virus-like particles containing codon-optimized AMA-1 of Plasmodium berghei

Abstract: BackgroundDespite the extensive endeavours, developing an effective malaria vaccine remains as a great challenge. Apical membrane antigen 1 (AMA-1) located on the merozoite surface of parasites belonging to the genus Plasmodium is involved in red blood cell invasion.MethodsInfluenza virus-like particle (VLP) vaccines containing codon-optimized or native (non-codon optimized) AMA-1 from Plasmodium berghei were generated. VLP-induced protective immunity was evaluated in a mouse model.ResultsMice immunized with V… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
36
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(39 citation statements)
references
References 19 publications
3
36
0
Order By: Relevance
“…At 6 d after P. berghei infection, parasites in red blood cells were collected and counted by flow cytometry (C, *P < .05). The error bars represent SEMresults were consistent with published reports 14,24. Compared to nonimmunized mice, MSP-8 VLPs-immunized mice showed significantly reduced parasitemia upon challenge infection, exactly corresponding with the purpose of this study.…”
supporting
confidence: 92%
See 2 more Smart Citations
“…At 6 d after P. berghei infection, parasites in red blood cells were collected and counted by flow cytometry (C, *P < .05). The error bars represent SEMresults were consistent with published reports 14,24. Compared to nonimmunized mice, MSP-8 VLPs-immunized mice showed significantly reduced parasitemia upon challenge infection, exactly corresponding with the purpose of this study.…”
supporting
confidence: 92%
“…We found that VLPs vaccination induces P. berghei-specific IgG and IgG2a antibody responses, T-cell responses and protection against malaria infection in mice. 14 Thus, we hypothesized that VLPs expressing the MSP-8 could play a critical role in inducing protection against malaria infection.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, VLPs effectively express robust immune responses in various cells of the humoral and cellular immune system without adjuvants [14,[16][17][18][19][20][21][22]. In our previous study, we evaluated the vaccine efficacies in mice immunized with VLPs containing apical membrane antigen 1 (AMA-1) of Plasmodium berghei [23]. AMA-1 VLP immunization effectively elicited humoral and cellular immune responses in mice [23].…”
Section: Introductionmentioning
confidence: 99%
“…In our previous study, we evaluated the vaccine efficacies in mice immunized with VLPs containing apical membrane antigen 1 (AMA-1) of Plasmodium berghei [23]. AMA-1 VLP immunization effectively elicited humoral and cellular immune responses in mice [23]. We sought to investigate in depth the immune response resulting from MSP-9 VLP immunization, using the advantage of the VLP vaccine platform.…”
Section: Introductionmentioning
confidence: 99%